2022
DOI: 10.1101/2022.03.09.22272158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct immune-effector and metabolic profile of CD8+ T Cells in patients with autoimmune polyarthritis induced by therapy with immune-checkpoint inhibitors

Abstract: Objectives: Rheumatic immune-related adverse events (irAE) such as (poly)arthritis in patients undergoing immune checkpoint inhibitor (ICI) treatment pose a major clinical challenge. ICI-therapy improves CD8+ T cell (CD8) function, but CD8 contribute to chronic inflammation in autoimmune arthritis (AA). Thus, we studied whether immune-functional and metabolic changes in CD8 explain the development of musculoskeletal irAE in ICI-treated patients. Methods: Peripheral CD8 obtained from ICI-treated patients with a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Further support for our findings comes from recent preclinical evidence that CD8 T cells from patients with R-irAE have a similar metabolic profile to CD8 T cells from patients with autoimmune arthritis and could therefore derive similar benefit from DMARDs typically used in classical RMDs. 51 Overall, these findings challenge the current strategy of a restrictive, second-line (b)DMARD use in the management of R-irAE. 1 Recent data from an observational study with a different methodological approach showed that the time to cancer progression in patients with de novo ICI arthritis was significantly shorter for patients treated with TNFi, and to lesser extent IL-6 inhibitors, compared with the csDMARD methotrexate.…”
Section: Discussionmentioning
confidence: 97%
“…Further support for our findings comes from recent preclinical evidence that CD8 T cells from patients with R-irAE have a similar metabolic profile to CD8 T cells from patients with autoimmune arthritis and could therefore derive similar benefit from DMARDs typically used in classical RMDs. 51 Overall, these findings challenge the current strategy of a restrictive, second-line (b)DMARD use in the management of R-irAE. 1 Recent data from an observational study with a different methodological approach showed that the time to cancer progression in patients with de novo ICI arthritis was significantly shorter for patients treated with TNFi, and to lesser extent IL-6 inhibitors, compared with the csDMARD methotrexate.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, our findings may also hold important implications in the emergence of irAEs observed in patients responding to ICB immunotherapy. Although activation of effector CD4 + and CD8 + T cells (55,56) as well as disturbances in Treg cells (57,58) are implicated in irAEs development, inflammatory monocytes are expected to contribute in a direct way through the secretion of pro-inflammatory cytokines and chemokines or indirectly via antigen processing and presentation. However, the role of emergency myelopoiesis in irAEs has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Upon TCR-mediated activation, CD8 switch to glycolysisin an mTORC1 dependent manner [36] and decrease OXPHOS, and in RA even naïve CD8 present such a metabolic profile [4]. Following activation of CD8 from arthritis patients, roughly 60% of ATP results from glycolysis [37] leaving the TCA cycle mainly for anabolic processes. Since aerobic glycolysis forces most of the pyruvate to be converted to lactate rather than to acetyl-CoA, the TCA cycle relies on acetyl-CoA resulting from FAO.…”
Section: Discussionmentioning
confidence: 99%